تحديد بعض العناصر المعدنية الثقيلة النذرة في أسماك الغبس Boopsboops في المياه الشاطئية لمدينة اللاذقية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2017)
تم التركيز في هذا البحث على تحديد تراكيز عنصري النحاس والرصاص(Cu& Pb) في عضلات وكبد أسماك النوع Boopsboopsفي كل من موقعي الدراسة (مصب نهر الكبير الشمالي و ميناء الصيد والنزهة) باستخدام تقنية الامتصاص الذري.بينت النتائج ارتفاع ملحوظ في تراكيز الرصاص خلال فصل صيف2014 في كل من النسيج العضلي والكبد للأسماك المدروسة (28.28ppm ,4.48ppm على التوالي) في مصب نهر الكبير الشمالي ومنطقة ميناء الصيد والنزهة (11.19ppm, 3.75ppm على التوالي)، وهذا يمكن أن يعود إلى اختلاف طبيعة الأنشطة البشرية ومصادر التلوث بهذا العنصر بين المنطقتين.أظهرت النتائج تغيرات فصلية ملحوظة لتراكيز عنصر النحاس ضمن النسيج الكبدي بين الأسماك المدروسة، حيث سجل أعلى تركيز في ميناء الصيد والنزهة5630.02ppm) )خلالفصل خريف 2014، والقيمة العليا 3402.27ppm في مصب نهر الكبير الشمالي خلال فصل الصيف. في حين لم تبدي نتائج تراكيز عنصر النحاس ضمن النسيج العضلي تغيرات فصلية وكانت التراكيز متقاربة نوعاً ما بين المحطتين، حيث سجلت أعلى التراكيز خلال فصل الصيف في كل من ميناء الصيد والنزهة (1497.70ppm) ومصب نهر الكبير الشمالي(1107.91ppm).تشير النتائج إلى تراكم العناصر المعدنية المدروسة (Cu&Pb) في الكبد مقارنة مع العضلات (يعزى ذلك إلى الاختلافات الفيزيولوجية في وظائف كل من العضوين) وإلى وجود علاقة ارتباط جيدة بين تغيرات تلك التراكيز في العضلات مع طول السمكة الأمر الذي يشير إلى زيادة تراكم هذه العناصر في هذه الأسماك مع زيادة النمو, مع ملاحظة ارتفاع تراكيز العناصر المدروسة عند الإناث أكثر من تلك المسجلة عند الذكور.This research focuses on determining elemental concentrations of copper and lead (Cu &pb) in the muscles and liver Boops boops kind of the estuary of the AL Kabeer Alshemaly River and the fishing port and the promenade using atomic absorption technique.The results showed a significant increase in the concentrations of lead during summer 2014 in each of the muscle tissue and the liver of the fish examined (28.28ppm& 4.48ppm, respectively) at the mouth of the estuary of the AL Kabeer Alshemaly River and the fishing port and the promenade (11.19ppm& 3.75ppm, respectively), and this could be due to the different nature of human activities and sources of pollution to this element between the two regions.The results showed a marked seasonal change in the concentration of copper within the liver tissue of fish studied, where the highest concentration in the fishing port and the promenade( 5630.02 ppm) in autumn 2014, the Supreme( 3402.27ppm) value in the AL Kabeer Alshemaly River the estuary of summer. While the results did not show the variable in concentrations of copper in muscle . Theconcentrations were comparable between the two stations somewhat, with the highest concentrations in the summer in Bouth the fishing port and the promenade 1497.70ppm) and(1107.91 ppm) the AL Kabeer Alshemaly River.Results indicate that the accumulation of the studied elements (Cu &pb) in the liver compared to muscle (and the reason is boiled physiological differences in the functions of each of the two members) and to the existence of a good correlation between the concentration in the muscle changes with the typical length of which points to increased accumulation of these elements in these fish with increased growth,Noting the high concentration of the studied elements in females more than those recorded in males.